Acute kidney injury in elderly intensive care patients from a developing country: Clinical features and outcome - Yokota, Laís Gabriela [UNESP]; Sampaio, Beatriz Motta [UNESP]; Rocha, Erica [UNESP]; Balbi, André Luís [UNESP]; Ponce, Daniela [UNESP] (Taylor & Francis, 2017)
Aim: The elderly are at high risk of acute kidney injury (AKI) because of structural and functional degeneration over time and with the aging of the population, the demand for intensive care unit (ICU) admission for older patients has risen recently. However, data from developing countries are scarce. This study aimed to describe the incidence of AKI in elderly patients admitted to ICU from a developing country, to determine the most frequent etiologies for renal impairment and identify its risk factors and outcome. Methods: All patients admitted to the ICU at a Brazilian teaching hospital for 12 consecutive months were followed prospectively from the time of admission until ICU discharge. Elderly was defined as aged >60 years and AKI was defined according to the Kidney Disease Improving Global Outcomes 2012 criteria. Multivariable logistic regression was used to adjust confounding and selection bias. Results: Two hundred elderly patients were included in the study. AKI incidence was 27% and the main etiology was sepsis (48.1%). At logistic regression, baseline creatinine (odds ratio [OR]=5.17, p<0.0001), Acute Physiology and Chronic Health Evaluation (APACHE) II (OR=1.20, p<0.0001), sepsis (OR=2.96, p<0.0001), and longer ICU stay (OR=1.68, p<0.0001) were associated with AKI in elderly patients. Baseline creatinine (OR=1.97, p=0.018), APACHE II (OR=1.29, p<0.0001), sepsis (OR=1.87, p<0.0001), and AKI severity (OR=2.57, p=0.027) were identified as predictors of death. Conclusion: AKI was frequent in elderly patients admitted to ICU from a developing country, and it was identified as a risk factor for death. Sepsis was an important risk factor for both AKI and mortality, similar to developed countries and in younger populations.
Keywords: Acute kidney injury; Elderly; Intensive care; Mortality